Greening mosquito coil manufacturing premise using cleaner production strategy / Poorni Letchumanan - Poorni, Letchumanan (2021)
Mosquito coil is an insect repellent used to kill or repel mosquitos. The mosquito coils are pesticides made from active ingredient, pyrethroid. Manufacturing of mosquito coils emits carbon dioxide to the environment that contribute to global warming. Thus, cleaner production strategy was implemented to green the chosen premise by reducing the emission of carbon dioxide. The cleaner production strategy is a preventive implementation for environmental protection by minimizing waste and emission and concurrently maximizing the product output. The factors used to calculate the carbon footprint includes the use of raw materials, fuels, electricity, and waste generated. A mosquito premise was selected to conduct the analysis. Based on the findings, the total carbon dioxide emitted from this premise is 61.9 tons of CO2 per month which is equivalent to 743 tons of CO2 per year for this premise. The production of mosquito coils per month required 564 × 103 kWh of electricity, 9,412 liters of diesel and a total of 1,540 kgs of the waste generation, inclusive of both solid waste and liquid waste. The release of carbon dioxide from the production of 1kg of mosquito coil was calculated and the outcome is particularly 0.565 kWh/ kg of mosquito coil from electricity consumption, 0.223 L/ kg of mosquito coil from diesel consumption, 0.015 kg/ kg of mosquito coil from solid waste generation and 0.0028 kg/ kg of mosquito coil from liquid waste generation. A total of twenty-eight (28) cleaner production options were identified and analysed to green the premise and eleven (11) cleaner production options amongst it were recommended based on priority measures to be implemented in the premise. This implementation can reduce carbon dioxide emission up to 46.8% which is equivalent to 29 tons of CO2 per month and 348 tonne of CO2 per year. This is equivalent of planting 11 thousand of trees per year. Total investment of RM 1,018,500 is needed to implement the recommended cleaner production options with a payback period of 4.8 years. Overall, it is recommended to manufacture a mosquito coil with less smoke as burning of mosquito coils releases carbon monoxide which is hazardous to environment. Mosquito coils that are more environmental-friendly can be manufactured by minimizing the use of raw materials and consumption of fuel and electricity in burning and processing the coils respectively. For future in-depth study, mosquito coils can be printed on a fibre roll paper instead of stamping the coils. This could be an effective way to green the premise.